Development of supported carbon-based catalyst for production of green diesel via deoxygenation of free fatty acids - Mohammed, Safa Gamal Nasser (2022)
The introduction of green diesel produced from the deoxygenation of non-edible feedstock is an alternative to conventional fuels. Hereby, the evaluation of catalytic deoxygenation of palm fatty acid distillate (PFAD) was carried out in an environment free of H2 to produce green diesel over mono-metallic (Co & Mn) and bimetallic catalysts (Co-Mo, Co-Ag, and Mo-Ag) supported on activated carbon (AC) derived from waste coconut shells. The biomass-derived AC prepared from waste coconut shells offers a competitive edge from the aspect of production cost. Based on the catalytic deoxygenation activity, the Co(10wt.)/AC catalyst showed a higher yield and selectivity than the Mn(10wt.)/AC. It was found that Co(10wt.)/AC catalysts exhibited high deoxygenation activity with hydrocarbon yield (C8-C20) was (71%) and (C15+C17) selectivity was (46%), attributed to strong acid–base-sites, which consecutively favouring C–O bond cleavage through the deoxygenation route. Further studies were carried out on bimetallic catalysts (Co-Mo, Co-Ag, and Mo-Ag) on AC supports. The effect of Mo in bimetallic catalyst Co10Mon/AC at various concentrations (n=5–20 wt.%) was investigated on the deoxygenation reactions performance. Based on the study results, the bimetallic catalyst Co(10wt.)-Mo(10wt.)/AC exhibited high catalytic performance with 92% hydrocarbon components (C8-C20) yield and 89% selectivity for (C15 +C17). This is owing to the good physicochemical properties of the catalyst, such as high strong acid-base sites, high crystallite size, good surface area and pore volume. Furthermore, it was stable until the sixth run maintaining hydrocarbon diesel components yield and selectivity of (C15 +C17) >80%. On the other side, the Co-Ag/AC and Mo-Ag/AC catalyst performed well in deoxygenation reactions, the optimization of a series of Co(10wt.%)-Ag(Z)/AC and Mo(10wt.%)-Ag(n)/AC catalysts (z & n: 5–20 wt.%) was also investigated. Astoundingly, the bimetallic catalyst Co(10wt.%)-Ag(10wt.%)/AC and Mo(10wt.%)-Ag(20wt.%)/AC exhibited a synergistic effect between the active metals Co-Ag and Mo-Ag with the activated carbon support (AC). The aforementioned catalysts have amazing physicochemical properties such as high surface area, high porosity, good dispersion of active metals on the support, strong acid and base density. These properties significantly facilitated the selective deoxygenation (deCOx) pathway of the fatty acids by exhibiting the greatest hydrocarbon (C8–C20) fractions yield of 92% & 93% and selectivity of (C15+C17) 95% & 90%. In addition, the Co(10wt.%)-Ag(10wt.%)/AC and Mo(10wt.%)-Ag(10wt.%)/AC catalysts also exhibit high stability and can be reused for up to eight cycles by producing hydrocarbons (C8 - C20) ~ 75-90 % and selectivity (C15+C17) ~ 70-90 %. Moreover, these catalysts showed an excellent coke inhibition with less than 5 wt.% of coke determined by TGA analysis. Thus, it can be believed a potentially promising catalyst for the production of green diesel, at the same time providing economic opportunities and added value to the palm oil industry. In summary, the bimetallic catalysts Co(10wt.%)-Ag(10wt.%)/AC and Mo(10wt.%)-Ag(10wt.%)/AC showed high catalytic activity represented in superior yield and selectivity besides distinguished reusability.